Overdue books at Leeds University Library. (September 2014) - Davies, Rachel; Sen, Barbara
As university libraries try to meet rising user expectations with limited resources, it is important to ensure that existing book stock is kept in circulation. This study investigated overdues at Leeds University Library, focusing on three key issues: reasons why users return their books overdue; effectiveness of current overdues policies; and suggested improvements to overdues procedures. The study was carried out using mixed methods: a print questionnaire of 181 library users, and qualitative interviews with 10 library staff members. The primary reasons for users' late return of books were forgetfulness and not realising that books were overdue. The library's current policies were considered easy to understand, but some problems were identified. These included: difficulty using online renewals; complaints about the reservations system; the large size of the student population; and user reluctance to seek help. Suggestions for improvement included increased use of e-books, text message reminders and better library publicity.